Detection of Norovirus in Children 0-5 Years Presenting with Acute Diarrhoea in Three Selected Tertiary Health Facilities in Jos, Plateau State, Nigeria - Jila Queen Torkwase; Nimzing Lohya; Chindah Evelyn Chingarum; Ajala Ese Kate; Ezekiel Tamar Amos; Abdulrazaq Madinah; Abel; Callum Ndubuisi (South Asian Journal of Research in Microbiology, 2026)
Norovirus is a global health concern and is considered a leading cause of acute gastroenteritis across all age groups, resulting in sporadic infections and epidemic or endemic outbreaks worldwide. Human norovirus infection accounts for substantial morbidity and mortality annually, particularly among children younger than 5 years. This study aimed to determine the prevalence of norovirus and the risk factors associated with infection among children presenting with acute diarrhoea in three selected tertiary health facilities in Jos. A descriptive cross-sectional study was conducted among paediatric inpatients and general outpatient attendees from January to November 2020. Consenting participants were recruited using simple random sampling, and a stool sample was collected from each child. Data were analysed using STATA statistical software, version 15. Norovirus antigen was detected in 61 of 184 samples using the MyBioSource Norovirus Antigen enzyme-linked immunosorbent assay, giving an overall prevalence of 33.2%. Plateau State Specialist Hospital accounted for the largest proportion of positive cases (68.9%), and the difference by facility was statistically significant. Among positive cases, 62.3% were male and 37.7% were female, although sex was not significantly associated with infection. The highest proportion of infections occurred among children aged 7–12 months (32.8%). Norovirus was detected throughout the study period, with the highest monthly proportion recorded in March (34.4%). Body temperature was significantly associated with norovirus infection, with 45.9% of positive cases occurring among children with temperatures of 38.0–38.9°C. The observed prevalence highlights the need to strengthen norovirus prevention, surveillance, and control interventions in Jos and to support evidence-informed consideration of future vaccination strategies. It is recommended that children and parents practice hand hygiene by washing frequently with soap and water, properly disinfect contaminated surfaces using bleach-based cleaners, and thoroughly wash fruits and vegetables before consumption to reduce risk of norovirus infection.